16 Systematic Analysis of Biotin Interference in Roche Chemistry Assays. (11th January 2018) - Gantt, Kibibi; Muthukumar, Alagar
Abstract: Introduction: The use of biotin supplements has increased manyfold in the last few years. This has led to several reports of biotin interference in laboratory results and, in some cases, misdiagnosis and treatment. Roche Diagnostics has a significant number of immunoassays with biotin-streptavidin architecture that are prone for interference by biotin. A detailed investigation of biotin interference in Roche immunoassays was conducted to address our clinicians' concerns. Methods: In the first phase, three adult volunteers (two women and one man) took USP-grade, over-the-counter biotin supplements (1, 5, and 10 mg doses), each dose for five days, starting with the lowest dose. Blood samples were collected for baseline and after the completion of each dose. In the second phase, two serum pools were made for each analyte (TSH, TT3, FT4, hCG, PTH, Troponin-T and NTproBNP). An aliquot from each pool was spiked with varying concentrations of biotin (1, 5, 10, 50, 100, 500, 1000 & 10, 000 ng/ml) and the extent of interference in each assay tested. Results: None of the over-the-counter doses of biotin in any of the Roche assays tested in all three volunteers had any interference. In phase 2, Troponin-T assay had no interference from biotin up to 100 ng/mL concentration, for TT3 and FT4 assays up to 10 ng/mL and for TSH assay up to 5 ng/mL of biotin concentration. At higher concentrations of biotin, the above assays had significant interference. NTproBNP, hCG and PTH assays had interference starting at 1 ng/mL of biotin concentration, and the interference was very significant beyond 5 ng/ml of biotin. Conclusion: Biotin interference in Roche immunoassays varied from assay to assay. Troponin-T assay was found to be robust, whereas NTproBNP, hCG, and PTH assays were sensitive to interference by biotin.